Simultaneous Effect of Diameter and Concentration of Multi-Walled Carbon Nanotubes on Mechanical and Electrical Properties of Cement Mortars: With and without Biosilica - Malumyan, Suren A.; Muradyan, Nelli G.; Kalantaryan, Marine A.; Arzumanyan, Avetik A.; Melikyan, Yeghvard; Laroze, David; Barseghyan, Manuk G. (Nanomaterials (Basel, Switzerland), 2024)
In this work, the effect of multi-walled carbon nanotubes (MWCNT1, MWCNT2, and MWCNT3) with different outer diameters and specific surface areas on the mechanical and electrical properties of cement mortar have been investigated. Various concentrations of MWCNTs were used (0.05, 0.10, and 0.15%), the effective dispersion of which was carried out by an Ultrasonic machine (for 40 min with 160 W power and a 24 kHz frequency) using a surfactant. Composites have been processed with a biosilica content of 10% by weight of cement and without it. Compressive strength tests were carried out on days 7 and 28 of curing. The 7-day compressive strength of samples prepared without biosilica increased compared to the result of the control sample (6.4% for MWCNT1, 7.4% for MWCNT2, and 10.8% for MWCNT3), as did those using biosilica (6.7% in the case of MWCNT1, 29.2% for MWCNT2, and 2.1% for MWCNT3). Compressive strength tests of 28-day specimens yielded the following results: 21.7% for MWCNT1, 3.8% for MWCNT2, and 4.2% for MWCNT3 in the absence of biosilica and 8.5%, 12.6%, and 6.3% with biosilica, respectively. The maximum increase in compressive strength was observed in the composites treated with a 0.1% MWCNT concentration, while in the case of 0.05 and 0.15% concentrations, the compressive strengths were relatively low. The MWCNT-reinforced cement matrix obtained electrical properties due to the high electrical conductivity of these particles. The effect of MWCNT concentrations of 0.05, 0.10, and 0.15 wt% on the electrical properties of cement mortar, especially the bulk electrical resistivity and piezoresistive characteristics of cement mortar, was studied in this work. At a concentration of 0.05%, the lowest value of resistivity was obtained, and then it started to increase. The obtained results show that all investigated specimens have piezoresistive properties and that the measurements led to a deviation in fractional change in resistivity.